The effect of using tangram media on ability to recognize color children - Zakiyah, Zakiyah; Yuwono, Joko (Universitas Negeri Yogyakarta, 2022)
Students with intellectual disabilities who have abilities below the average, so that it has an impact on their ability to participate in learning in class. The understanding of students with intellectual disabilities about color is still low. The lack of attractiveness of the media used in learning to recognize colors, causing saturation in students. This study aims to describe the effect of using tangram media on students' ability to recognize colors before and after being treated. The research subjects were grade 3 with 3 students at SLB Negeri Seduri Mojokerto. This study uses an experimental approach with a pre-experimental research design type one group pretest-posttest. Data collection techniques in the form of tests and observations. The test was conducted to determine the students' ability to recognize colors before and after using tangram media, while observations were made to determine the implementation of learning using tangram media in the classroom. The results showed that there was a significant increase in the use of tangram media for color recognition in students with intellectual disabilities. The use of tangram media is needed by students with intellectual disabilities because it has an interesting effect in recognizing colors.